Alguns aspectos funcionais da articulação temporomandibular. - Marques, C. G.; Cabrera, M. A.; Cabrera-Peralta, C. (My University, 1989)
The authors emphasize the some functional characteristics of the Temporomandibular join, TMJ, and were made comparative study of the auscultatory and sphymografic techniques to TMJ examination. The findings shown that the auscultatory technique furnished important dates to preliminary diagnosis of the TMJ disfunction.
Some functional aspects of the temporomandibular joint
Keywords: auscultation; human; myofascial pain; pathophysiology; sound; tooth occlusion; Auscultation; Dental Occlusion; English Abstract; Human; Sound; Temporomandibular Joint Dysfunction Syndrome